The Influence of Leadership Style and Motivation on Employee Performance - Putri Ayu Kartini; Bayu Airlangga Putra; Hermien Tridayanti; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2021)
In today's era of globalization, company competition is growing rapidly to find new ideas to achieve company goals. This research was conducted at Dairy Queen Surabaya with the aim of knowing (1) the influence of leadership style on employee performance, (2) the effect of motivation on employee performance, and (3) the effect of leadership style and motivation together on employee performance. This study is a quantitative study with a sample of 30 respondents and a questionnaire was used to collect data related to the variables in this study. Using the validity test and reliability test using SPSS 18.0 for Windows. Furthermore, classical assumption test includes multicollinearity test and heteroscedasticity test. While testing the hypothesis in this study using multiple regression analysis and the coefficient of determination and hypotheses. Data analysis using multiple linear regression analysis technique and the results of this study are leadership style, motivation partially and simultaneously significant effect on employee performance.